2004
DOI: 10.1186/1471-2334-4-40
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Schistosoma haematobium infection, impact of praziquantel treatment and re-infection after treatment in a cohort of schoolchildren from rural KwaZulu-Natal/South Africa

Abstract: Background: Schistosomiasis is one of the major health problems in tropical and sub-tropical countries, with school age children usually being the most affected group. In 1998 the Department of Health of the province of KwaZulu-Natal established a pilot programme for helminth control that aimed at regularly treating primary school children for schistosome and intestinal helminth infections. This article describes the baseline situation and the impact of treatment on S. haematobium infection in a cohort of scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 18 publications
9
72
3
Order By: Relevance
“…Although praziquantel was efficacious against both S. mansoni and S. haematobium infections with little or no evidence of possible resistance as indicated in this report (Guyatt et al, 2001;Degu et al, 2002;Saathoff et al, 2004a;Midgzi et al, 2008;), other antischistosomal drugs investigated such as oxamniquine, and antimalarial drugs eg. artesunate, amodiaquine and sulphadoxine-pyremethamine were also reasonably effective (Thiong'o et al, 2002;Inyang-Etoh, 2004;Boulanger et al, 2007;Inyang-Etoh et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although praziquantel was efficacious against both S. mansoni and S. haematobium infections with little or no evidence of possible resistance as indicated in this report (Guyatt et al, 2001;Degu et al, 2002;Saathoff et al, 2004a;Midgzi et al, 2008;), other antischistosomal drugs investigated such as oxamniquine, and antimalarial drugs eg. artesunate, amodiaquine and sulphadoxine-pyremethamine were also reasonably effective (Thiong'o et al, 2002;Inyang-Etoh, 2004;Boulanger et al, 2007;Inyang-Etoh et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the findings of this review indicated that benzimidazoles exhibited considerable cure rates and egg reduction rates particularly against A. lumbricoides and hookworms (Guyatt et al, 2001;Jinabhai et al, 2001;Saathoff et al, 2004b;Adugna et al, 2007;Kihara et al, 2007;) and aside from reducing the load of worms, benzimidazole treatment has been shown to improve the nutritional status and cognitive development of children infected with A. lumbricoides, T. trichiura, and hookworms and reduces hookworm associated anaemia in children (Albonico et al, 1996;Stoltzfus et al, 1998). On the other hand studies reviewed indicated that a single oral dose of 40 mg of praziquantel per kg of body weight was safe, showed no or only a few but transient side effects, but resulted in high parasitological cure and egg reduction rates against both S. mansoni and S. haematobium (Berhe et al, 1999;Taylor et al, 2001;Guyatt et al, 2001;Degu et al, 2002;Saathoff et al, 2004a;Midzi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies using a variety of diagnostic methods in various at-risk populations have shown a wide variance in schistosomiasis prevalence in endemic countries. Twenty per cent of adults in rural Nigeria [16], 40% of adults in rural Zambia [17], and 68% of children in rural South Africa [18] were infected with schistosomiasis. Among African migrants to Australia, 12% of those attending general practice in Melbourne [19] and 7% of those attending the Migrant Health Unit in Perth [20] were found to be infected with schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,34,40 The effects on child development may result in a generation of adults disadvantaged by the irreversible consequences of this infection. 42 Endemic areas were identified using the Atlas of Bilharzia in Southern Africa 23 which helped to provide estimates of the population at risk of the disease and to adequately plan for the control programme.…”
Section: Volume 111 | Number 11/12mentioning
confidence: 99%
“…4 The endemic areas in South Africa are in the north and the east, covering about a quarter of the country. 5 The most common species in South Africa is S. haematobium . School-aged children usually present the highest prevalence and intensity of infection.…”
Section: Introductionmentioning
confidence: 99%